The Relation Between Teacher’s Performance and Student’s Learning Motivation During Hybrid Learning in Elementary School - Fadhila, Priska; Hidayati, Dian (Universitas Pendidikan Indonesia, 2021)
This studies aims to know the relation between teacher performance and student’s learning motivation during hybrid learning model in elementary school. This research use correlation type of quantitative research by using product moment correlation. The sample of this studies use random sampling technique and follow Slovin rules to get the quantity of sample from two elementary school, SD Muhammadiyah Kadisoka and SD Muhammadiyah Bayen which the school that have been implemented hybrid learning. The primary data collected from Likert’s scale that modified to 4 score to avoid neutral answer. The data analyzed by SPSS IBM Statistic for Windows 25 Version. The result of research is there is a positive relation between teacher performance and student’s learning motivation. The higher teacher’s performance, the higher student’s learning motivation.